The Antifungal Activity of Artesunate toward Candida albicans: Two Opposite Activities - MOHAMMAD RIZKI F ADHIL PRATAMA; DARYONO HADI TJAHJONO; TUTUS GUSDINAR (Microbiology Indonesia, 2019)
The artemisinin and its derivatives antifungal activity continue to be an interesting research object, with the potential shown to be developed as an antifungal compound. Artesunate, one of the artemisinin derivatives known to have antifungal activity against various pathogenic fungi, including Candida albicans. This study aims to determine the effect of artesunate on antifungal activity toward C. albicans in vitro at concentrations below 1 mg -1m L . The method used is yeast-plate count, with a parameter of observation were the number of C. albicans colonies viable after exposure with artesunate for five days. The concentration of artesunate used was divided into -1 -2 -3 -4 -1si x groups, which were 10; 1; 10 ; 10 ; 10 ; and 10 mg mL . Compared to control, a significant decrease in -1c olony counts was only shown at the highest concentration of 10 mg mL . Interestingly, at the lowest -4 -1c oncentration of 10 mgmL , it showed an increase in a number of colonies almost twice of the blank. These results suggest that while at higher concentration of artesunate may inhibit the growth of C. albicans, a lower concentration of artesunate may stimulate their growth.